A nonintrusive control strategy using voltage and reactive power for distribution systems based on PV and the nine-zone diagram. (February 2019) - Dou, Xiaobo; Duan, Xiangmei; Hu, Qinran; Shen, Lu; Wu, Zaijun
Highlights: The proposed control strategy using PVs to cooperate with NDC unilaterally. It does not change the original control strategy in VQC system, which makes it easy to achieve in the project and reduces project investment. Voltage feedback is applied in the reference value track to eliminate deviations. Voltage and reactive power violations can be solved in a timely and economical way compared to the NDC strategy. Abstract: The increasing penetration of photovoltaics (PVs) and fluctuating load exacerbate the risk of voltage and reactive power violations in distribution systems. The conventional regulation strategy is based on the nine-zone diagram control (NDC), which is difficult to quick response and meet the requirement with high precision. Utilizing the delay of NDC, a nonintrusive control strategy of voltage and reactive power for distribution systems is developed in this paper. The proposed control strategy uses the ability of PV to cooperate with traditional devices without changing the original NDC strategy, which makes it easy to implement and extend in the project. First, a time-series control architecture is developed to reduce the number of traditional devices and eliminate voltage violations. Then, by using the sensitivity values of multiple devices, the reactive power output of PVs is calculated, and the voltage reference value in PV inverter control (PVC) horizon can be tracked based on feedback. A case study is carried out on an IEEE 33-node system to illustrate the effectiveness of the proposed method. It is shown that PV can be used as a continuous reactive power source to realize fast and accurate regulation and the proposed method can improve adjustment accuracy and reduce the operation of conventional equipment compared to the NDC.